An innovative method of surgical excision of duodenal diverticulum in a 17-year-old girl - Korycka, Marta; Nogal, Piotr; Sosnowska, Patrycja; Noskiewicz, Jakub; Mańkowski, Przemysław (Pediatria Polska - Polish Journal of Paediatrics, 2018)
The first well-documented case of the duodenal diverticulum (DD) was presented by Morgagni in 1762. In 1913 Case presented four cases of radiologically diagnosed DD. The first surgical resection of the duodenal diverticulum took place in 1915 and was performed by Key. The aetiology of the duodenal diverticula is not clear and remains controversial. The existence of the locus minoris resistentiae in the duodenal wall may be the place of mucosal or submucosal tissue layer herniation through the muscular defect. Duodenum is the second most common location of diverticula in the gastrointestinal tract. They appear in about 23% of the population and are rarely found in children. Surgical treatment is applied only if complications occur. We present a case of a 17-year-old female treated surgically with the use of a minimally invasive laparoscopic method combined with endoscopic control of the surgical field.